Al-Quran as a source of knowledge : a theological perspective in early Islam - Ishak, Mohd. Shuhaimi (LAP Lambert Academic Publishing, 2013)
The idea of discussing the concept of faith in a thesis is to show the reliance of this concept to the absolute authority of the Quran and supplemented by the explanations of theSunnah. All along the Quran exerted a steady and moderate influence and thus eliminates all extremes fanatic notions in the conceptions of faith. Nothing demonstrates this more convincingly and decisively than the Quran. The book aims at analysing the facts of the earlier stage of Islam on the problems on the concept of faith, and the later stage the rise of the Sunni scholars and jurists often scarcely distinguished in theearly centuries, realised that being plainly subordination to Allah is absolute. They rose to the occasion and led the majority of the Muslims to a remarkable level of understanding and unity in the main issues of faith. The book consists of six chapters. The first chapter is the introduction. The chapter shall consist of a general statement, the objective of the study, problem statement, research questions and literature review. The second chapter deals with the emergenceof sects in early Islam: the period after the death of the Prophet (s.a.w), the early caliphate, the Kharijite movement, the appearance of the Shia, the opposition toKharijite movements, the Qadarites and Jabrites, the Mutazilites and conclusion. The third chapter deals with the theological positions of varioussects: theology of the Kharijites, theology of Murjiites, theology of the Shia, theology of the Qadarites and Jabrites, Mutazilite's theology and conclusion. Chapter four will discuss the consolidation of Sunnism: the emergence of Sunnism, aftermath of the Mihna,the rise of Mutakallimun, the contribution of Sunnite theologians and conclusion.